Long-term efficacy and safety of osilodrostat in patients with Cushing’s disease: results from the LINC 4 study extension - Gadelha, Mônica; Snyder, Peter J.; Witek, Przemysław; Bex, Marie; Belaya, Zhanna; Turcu, Adina F.; Feelders, Richard A.; Heaney, Anthony P.; Paul, Michaela; Pedroncelli, Alberto M.; Auchus, Richard J. (Frontiers in Endocrinology, 2023)
Objective: To evaluate the long-term efficacy and safety of osilodrostat in patients with Cushing’s disease. Methods: The multicenter, 48-week, Phase III LINC 4 clinical trial had an optional extension period that was initially intended to continue to week 96. Patients could continue in the extension until a managed-access program or alternative treatment became available locally, or until a protocol amendment was approved at their site that specified that patients should come for an end-of-treatment visit within 4 weeks or by week 96, whichever occurred first. Study outcomes assessed in the extension included: mean urinary free cortisol (mUFC) response rates; changes in mUFC, serum cortisol and late-night salivary cortisol (LNSC); changes in cardiovascular and metabolic-related parameters; blood pressure, waist circumference and weight; changes in physical manifestations of Cushing’s disease; changes in patient-reported outcomes for health-related quality of life; changes in tumor volume; and adverse events. Results were analyzed descriptively; no formal statistical testing was performed. Results: Of 60 patients who entered, 53 completed the extension, with 29 patients receiving osilodrostat for more than 96 weeks (median osilodrostat duration: 87.1 weeks). The proportion of patients with normalized mUFC observed in the core period was maintained throughout the extension. At their end-of-trial visit, 72.4% of patients had achieved normal mUFC. Substantial reductions in serum and LNSC were also observed. Improvements in most cardiovascular and metabolic-related parameters, as well as physical manifestations of Cushing’s disease, observed in the core period were maintained or continued to improve in the extension. Osilodrostat was generally well tolerated; the safety profile was consistent with previous reports. Conclusion: Osilodrostat provided long-term control of cortisol secretion that was associated with sustained improvements in clinical signs and physical manifestations of hypercortisolism. Osilodrostat is an effective long-term treatment for patients with Cushing’s disease. Clinical trial registration: ClinicalTrials.gov, identifier NCT02180217